Comparison between a new ultrasound probe with a capacitive micromachined transducer (CMUT) and a traditional one in musculoskeletal pathology. (December 2020) - Draghi, Ferdinando; Lomoro, Pascal; Bortolotto, Chandra; Mastrogirolamo, Luca; Calliada, Fabrizio
Background: The capacitive micromachined ultrasound transducer (CMUT) is a new ultrasound (US) probe manufactured by state-of-the-art cutting-edge semi-conductor micromachined electro-mechanical systems (MEMS) technology. Purpose: To demonstrate the peculiar characteristics of each probe and the limitations that should be improved. Material and Methods: This study was performed from March to April 2018. The only inclusion criterion was the presence of disease, so all patients with musculoskeletal, skin, and subcutaneous pathology were included. A total of 66 patients entered this study. The exams of each patient, with both probes, were evaluated retrospectively and independently by three radiologists. Panoramicity of the images, the definition of superficial structures (<2 cm of depth), the definition of deep structures (>2 cm), and Doppler signal were assessed. A 5-point scale was used for each parameter. Results: A total of 89 pathologies were detected. The mean of score for 4G-CMUT was higher than L64 for the panoramicity of the images and the definition of the deep structures. Instead, the mean score for L64 was higher than for 4G-CMUT in the evaluation of superficial structures and Doppler signal. A statistically significant difference was found ( P < 0.05). Conclusion: CMUT is a breakthrough in US technology. It allows the use of a single probe for different US examinations. The musculoskeletal, skin, and subcutaneous US can be evaluated with a piezoelectric linear transducer or CMUT. In the present study, the overall diagnostic performance was similar. Improvements in CMUT will provide even more dynamic and flexible imaging capabilities by a transducer, with a wider bandwidth.